Cannabis sativa y la metodología del marco lógico para el desarrollo de proyectos de inversión pymes en alimentos. norte de Santander, Colombia. - Francisco Raúl Arencibia-Pardo; Jazmin Anai Ávila-Treviño; Belisario Peña-Rodríguez (Mundo Fesc)
This research aims to identify Cannabis sativa as a source of investment projects for MSMEs in the alternative, healthy, and competitive food sector in Villa del Rosario, Norte de Santander Department, Colombia. To achieve this goal, the research proposes to identify the unmet need for training among the agricultural population to participate in industrial ventures in the region and, above all, the importance of stakeholders as a regional influence.